ANTISEDEN KEPUTUSAN PEMBELIAN KONSUMEN TISU MEREK ALFAMART - Suhaya Suhaya (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
Customer decisions are crucial, from the business aspect it is a potential moment. So the right step for the company is to give the best, like promotion and good image. This research is intended to analyze the independent variables. How does it affect the dependent variable (purchasing decision). So we know a number that can be used to make decisions. To prove the purpose of the research, at least a quantitative approach is used. Data collection techniques using primary (direct), by asking a list of questions. Data were analyzed using linear regression with several stages, including the validity test, the classic assumption test, and the hypothesis test. The results of the study suggest, consumer decisions in buying greatly influenced by many factors, but promotion has a big contribution.